Synthesize of alginate/chitosan bilayer nanocarrier by CCD-RSM guided co-axial electrospray: A novel and versatile approach. (February 2019) - Tsai, Shawn; Ting, Yuwen
Abstract: To improve oral bioavailability of bioactive compounds, nano-scopic carrier systems with multiple layers has become the recent popular trend. The preparation of the nano-sized bilayer system usually requires multiple operations and intense energy input. For better efficiency, co-axial electrospraying was developed as the novel method to manufacture dual-layered nanocarrier. To improve the versatility of the production, the co-axial electrospray process was further guided by CCD-RSM (Central Composite Design-Response Surface Methodology) when generating bilayer nanocarrier. Chitosan and alginate were arranged into the core and shell part of the carrier, respectively. Through the RSM analysis, the optimum processing parameters to prepare the chitosan/alginate bilayer carrier with 112.1 ± 35.2 nm diameter were determined. The surface morphology and dual layer structure were characterized microscopically. In summary, this work has successfully developed a novel and versatile mean to efficiently produce bilayer nanocarrier using co-axial electrospray combine with CCD-RSM analysis. These results could serve as a firm foundation to promote electrospray technique for the preparation of oral carrier system containing bioactive components. Graphical abstract: Unlabelled Image Highlights: Successfully developed the CCD-RSM guided co-axial electrospray process. Chitosan/alginate nanocarrier was synthesiszed using co-axial electrospray technique. Chitosan/alginate bilayer particle was produced without additional binding agent. Chitosan/alginate bilayer nanocarrier was produced using simple one-step processing. High versatility and convertibility to accommodate different processing needs.